2020
DOI: 10.1038/s41398-020-01070-3
|View full text |Cite
|
Sign up to set email alerts
|

Early-life stress alters affective behaviors in adult mice through persistent activation of CRH-BDNF signaling in the oval bed nucleus of the stria terminalis

Abstract: Early-life stress (ELS) leads to stress-related psychopathology in adulthood. Although dysfunction of corticotropin-releasing hormone (CRH) signaling in the bed nucleus of the stria terminalis (BNST) mediates chronic stress-induced maladaptive affective behaviors that are historically associated with mood disorders such as anxiety and depression, it remains unknown whether ELS affects CRH function in the adult BNST. Here we applied a well-established ELS paradigm (24 h maternal separation (MS) at postnatal day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 103 publications
(153 reference statements)
2
22
0
Order By: Relevance
“…FKBP51 and the ovBNST play a pivotal role in stress-induced anxiety disorders ( Ising et al, 2008 ; Kang et al, 2012 ; Kim et al, 2013 ; Klengel et al, 2013 ; Scheuer et al, 2016 ; Hu et al, 2020a , b ). However, the precise function of FKBP51 in the ovBNST and its role in anxiety remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FKBP51 and the ovBNST play a pivotal role in stress-induced anxiety disorders ( Ising et al, 2008 ; Kang et al, 2012 ; Kim et al, 2013 ; Klengel et al, 2013 ; Scheuer et al, 2016 ; Hu et al, 2020a , b ). However, the precise function of FKBP51 in the ovBNST and its role in anxiety remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, chronic stress and acute optogenetic activation of the ovBNST increased anxiogenic behaviors ( Hu et al, 2020a ). Moreover, early life stress resulted in a long-lasting activation of CRH signaling in the mouse ovBNST, leading to potential maladaptive changes in ovBNST function in adulthood ( Hu et al, 2020b ). The ovBNST is therefore a promising region with regard to anxiety disorders, since it is strongly involved in mediating anxiety-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic RS leads to neuroplastic changes, including increased BNST volume and dendritic arborization, that facilitate avoidance behavior in male rats ( Vyas et al, 2003 ). Different chronic stress paradigms can also cause upregulation of glutamate ( Dabrowska et al, 2013 ; Hu et al, 2020b ), GABA ( Ventura-Silva et al, 2012 ), and NMDA ( Ventura-Silva et al, 2012 ; Dabrowska et al, 2013 ) receptors in the BNST, altering responses to both excitatory and inhibitory inputs ( Ventura-Silva et al, 2012 ). Both chronic social isolation and chronic corticosterone administration induce long term depression (LTD) in glutamatergic anterolateral BNST neurons and blunt long term potentiation (LTP) in anterodorsolateral BNST neurons ( Conrad et al, 2011 ).…”
Section: Neuroplasticity In the Corticotropin-releasing Factor-signal...mentioning
confidence: 99%
“…Neuroplastic changes in the BNST are necessary for fear learning, wherein exposure to sustained or unpredictable aversive stimuli causes changes at the synaptic level ( Conrad et al, 2011 ; Haufler et al, 2013 ; Goode and Maren, 2017 ; Goode et al, 2019 ). Several recent studies have demonstrated synaptic and electrophysiological changes after exposure to chronic stress ( Makino et al, 1994 ; Vyas et al, 2003 ; Forray and Gysling, 2004 ; Hammack et al, 2009 ; McElligott et al, 2010 ; Conrad et al, 2011 ; Ventura-Silva et al, 2012 ; Dabrowska et al, 2013 , 2016 ; Partridge et al, 2016 ; Snyder et al, 2019 ; Hu et al, 2020a , b ). Much of these changes occur within corticotropin-releasing factor (CRF)-expressing neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation